Pengaruh Insektisida Klorpirifos Terhadap Struktur Histologi Intestinum Ikan Wader Pari (Rasbora lateristriata Bleeker, 1854) - Jerizqa Ayu Fajar Nita; Bambang Retnoaji (Graduate School Bogor Agricultural University (SPs IPB), 2022)
Chlorpyrifos is one of commonly used insecticides. However, the use of insecticides in agriculture has negative impacts including lethal effect to non-target organisms. Wader pari fish is a type of freshwater fish that lives in rice fields or rivers and can be used as an indicator of water pollution. The purpose of this study was to determine the intestinal histological structure, the histopathological effect of chlorpyrifos on intestine, and population number of goblet cells, respectively. The treatment concentration of 0.001; 0.005; and 0.01 ppm were determined by preliminary trial and exposed for 168 hours. Fish behavior and water quality were monitored. The fish were still alive until the last day of exposure were then made intestinal histological preparations using the paraffin method and staining with Haematoxylin Eosin (HE), Mallory Acid Fuchsin (MAF), Periodic Acid Schiff (PAS). The results showed that the histological structure of the wader pari intestine consisted of mucosal tunica, submucosal tunica, muscularis tunica, and serous tunica. Furthermore, chlorpyrifos has a significant effect on population number of goblet cells. The intestine damages were edema, vacuolization, cloudy swelling, hemorrhage, lysis, and fusion of vili. It could be concluded that chlorpyrifos caused intestinal damage in wader pari fish.